ChemInform Abstract: Synthesis of Isatins by I2/TBHP Mediated Oxidation of Indoles. Issue 48 (2nd December 2014) - Zi, You; Cai, Zhong‐Jian; Wang, Shun‐Yi; Ji, Shun‐Jun
Abstract A convenient, simple, and metal‐free protocol for the synthesis of isatins by direct oxidation of commercially available indoles under mild conditions is developed.